Springboards and Barriers to Creative Risk‐Taking and Resolve in Undergraduate Interior Design Studios. Issue 4 (17th October 2015) - Ellis, Natasha; Meneely, Jason
ABSTRACT: This study identified springboards and barriers to creative risk‐taking that interior design students perceive in their studio courses. Three research questions were posed: (1) What personality traits associated with creative risk‐taking do interior design students display? (2) What springboards and barriers to creative risk‐taking do interior design students perceive in their studio courses? (3) How do classroom expectations differ between safekeeping and risk‐taking students? Participants included ( n = 66) undergraduate interior design students from a Council for Interior Design Accreditation program located in the southeastern United States. TheNEO Personality Inventory Revised was used to profile personality traits while a locally developed survey identified student perceptions of creative risk‐taking in studio. Using self‐reported and faculty ratings of risk‐taking propensity, each student was categorized into either a safekeeping or risk‐taking group for data analysis. Private interviews ( n = 18) were conducted with selected students from each group to gain further insight into their perceptions of risk. Findings indicated that the sample displayed higher levels of Extraversion, Openness, and lower levels of Agreeableness than normative populations. Safekeeping students expressed a need for compassionate support, encouragement, and daily feedback from their instructors, whereas risk‐takers wanted instructors who challenged and criticized their work while providing feedback on a less regular basis. Safekeepers favored more detailed project structures with clear requirements, whereas risk‐takers preferred a loose project structure with broad instructions and limitations. Educational implications and curricular strategies surfacing from the findings are discussed.